INTER-LAYER BIT ALLOCATION FOR SCALABLE HIGH-EFFICIENCY VIDEO CODING - Võ Phương Bình (Tạp chí Khoa học Đại học Đà Lạt)
Bit allocation is essential for a video encoder to accurately control the generated bits, and thus greatly influences the visual quality. In this paper, an improved bit allocation algorithm is proposed at the frame level for the emerging Scalable High-efficiency Video Coding (SHVC) standard. At the spatial base and enhancement layers, the bit budget is derived jointly from the hierarchical level and the visual complexity of the current frame, where the latter is measured by the inter-layer predicted MAD (Mean Absolute Difference) to allocate the bit budget of each frame. Experimental results show that the proposed method achieves more accurate bitrates with higher visual quality in the average PSNR up to 1.40dB, and controls buffer occupancy more satisfactorily, as compared with the-state-of-the-art approaches in the literature.